An Indonesian Democracy: limits of a majoritarian democracy - Ben Kristian Citto Laksana (Parahyangan Center for International Studies, 2016)
Indonesia has continuously been praised as a successful post-authoritarian country transitioning to democracy. However, seeing the numerous human rights violations in the past decade alone especially towards alternative political, religious and sexual identities, the success of democracy in Indonesia has been put under the spotlight. This raises the question of the development of democracy and the use of democracy in Indonesia in practicing and upholding principles of social equality for all. In this article I wish to provide an overview of majoritarian democracy, a form of democracy that is understood and practiced in Indonesia. A form of democracy that rather than upholding values that safeguards individual rights and diversity, may in fact undermine religious and cultural diversity, enforcing a homogenized national culture and values, which in return may engender human rights violations in the name of national security that it in itself is defined by the majority.